Long non-coding RNA Loc105611671 promotes the proliferation of ovarian granulosa cells and steroid hormone production upregulation of CDC42 - Wang, Jinglei; Chen, Hanying; Zhang, Yongsheng; Shen, Hong; Zeng, Xiancun (Frontiers in Veterinary Science, 2024)
Granulosa cells (GCs) are essential for follicular development, and long non-coding RNAs (LncRNAs) are known to support the maintenance of this process and hormone synthesis in mammals. Nevertheless, the regulatory roles of these lncRNAs within sheep follicular GCs remain largely unexplored. This study delved into the influence of a Loc105611671, on the proliferation and steroid hormone synthesis of sheep ovarian GCs and the associated target genes in vitro. Cell Counting Kit-8 (CCK-8) gain-of-function experiments indicated that overexpression of Loc105611671 significantly boosted GCs proliferation, along with estrogen (E2) and progesterone (P4) levels. Further mechanistic scrutiny revealed that Loc105611671 is primarily localized within the cytoplasm of ovarian granulosa cells and engages in molecular interplay with CDC42. This interaction results in the upregulation of CDC42 protein expression. Moreover, it was discerned that increased CDC42 levels contribute to augmented proliferation of follicular granulosa cells and the secretion of E2 and P4. Experiments involving co-transfection elucidated that the concurrent overexpression of CDC42 and Loc105611671 acted synergistically to potentiate these effects. These findings provide insights into the molecular underpinnings of fecundity in ovine species and may inform future strategies for enhancing reproductive outcomes.